2022
DOI: 10.1002/14651858.cd011775.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Child protection training for professionals to improve reporting of child abuse and neglect

Abstract: Child protection training for professionals to improve reporting of child abuse and neglect (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 143 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…It has been emphasized that students' reporting behaviors are affected by their level of knowledge about the subject, and students should be trained to develop their competencies in identifying, reporting, and preventing abuse (Jeon et al, 2022; McClure et al, 2020; Tek & Karakaş, 2021). A Cochrane review by Walsh et al (2022) highlighted the need for training professionals, including nurses, to be able to perform their reporting duties. However, a study reported that the trainings did not provide the authorized reporters with comprehensive information on the definitions, examples, and indicators of the main types of childhood maltreatment, and it was emphasized that a curriculum should be developed in this regard (Baker et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has been emphasized that students' reporting behaviors are affected by their level of knowledge about the subject, and students should be trained to develop their competencies in identifying, reporting, and preventing abuse (Jeon et al, 2022; McClure et al, 2020; Tek & Karakaş, 2021). A Cochrane review by Walsh et al (2022) highlighted the need for training professionals, including nurses, to be able to perform their reporting duties. However, a study reported that the trainings did not provide the authorized reporters with comprehensive information on the definitions, examples, and indicators of the main types of childhood maltreatment, and it was emphasized that a curriculum should be developed in this regard (Baker et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Professionals are not always familiar with the behavioral and psychological signs characteristic of other forms of maltreatment, such as emotional neglect or certain forms of sexual assault. The more the child is endangered, the greater the tendency to report (Lagerberg, 2004; Walsh et al , 2022). Fraser et al (2010) also indicated that emotional violence is significantly underreported.…”
Section: Discussionmentioning
confidence: 99%
“…Professionals are not always familiar with the behavioral and psychological signs characteristic of other forms of maltreatment, such as emotional neglect or certain forms of sexual assault. The more the child is endangered, the greater the tendency to report (Lagerberg, 2004;Walsh et al, 2022). Fraser et al (2010) 2015) report showed that although the ministries of education, health and the economy have taken measures in recent years to train employees who are expected to identify such minors, the ministries did not map the yet unmet needs, and some have not set quantitative targets for the coming years.…”
Section: Lack Of Proper Trainingmentioning
confidence: 99%
“…Since the early 2000s, states have been implementing policies related to the prevention of CSA. For example, policies encouraging or mandating schools to provide training and education to adults (eg, teachers, other staff and parents) or children about the signs, symptoms and strategies for preventing CSA have been reported 18. One such policy is Erin’s Law, originally passed in the state of Illinois in 2011.…”
Section: Introductionmentioning
confidence: 99%